Control of topoisomerase II activity and chemotherapeutic inhibition by TCA cycle metabolites - Lee, Joyce H.; Mosher, Eric P.; Lee, Young-Sam; Bumpus, Namandjé N.; Berger, James M. (Cell chemical biology, 2022)
Topoisomerase II (topo II) is essential for disentangling newly replicated chromosomes. DNA unlinking involves the physical passage of one duplex through another and depends on the transient formation of double-stranded DNA breaks, a step exploited by frontline chemotherapeutics to kill cancer cells. Although anti-topo II drugs are efficacious, they also elicit cytotoxic side effects in normal cells; insights into how topo II is regulated in different cellular contexts is essential to improve their targeted use. Using chemical fractionation and mass spectrometry, we have discovered that topo II is subject to metabolic control through the TCA cycle. We show that TCA metabolites stimulate topo II activity in vitro and that levels of TCA flux modulate cellular sensitivity to anti-topo II drugs in vivo. Our work reveals an unanticipated connection between the control of DNA topology and cellular metabolism, a finding with ramifications for the clinical use of anti-topo II therapies. [Display omitted] •TCA cycle intermediates stimulate the strand passage activity of S. cerevisiae topo II•Stimulation of enzyme activity by TCA metabolites is specific to eukaryotic topo IIs•Topo II activity and drug response is impacted by changes in TCA cycle flux in cells Lee et al. purify yeast metabolites that show activity against eukaryotic topoisomerase II (topo II). LC-MS/MS analysis identifies TCA cycle intermediates as stimulators of topo II activity. Modulating TCA cycle flux affects the cytotoxicity of topo II-targeting drugs, indicating that TCA cycle metabolism regulates topo II function in cells.